ENSURING GREEN GROWTH THROUGH INCREASING EFFICIENCY IN THE INDUSTRIAL SECTOR (The Conference Hub, 2025)
Currently, the processes of economic development are rapidly accelerating on a global scale. The principles of digital transformation, innovative technologies, and the rational use of resources are deeply penetrating all sectors of the economy, particularly the industrial sector. In particular, the widespread use of information and communication technologies in production processes allows the practical implementation of the “green growth” concept by improving efficiency, ensuring energy saving, and reducing waste.